CONTINUITY OF ECOLOGICAL AND GEOGRAPHICAL EDUCATION IN ECONOMIC UNIVERSITIES - Il’gizar T. Gaisin; Renat I. Gaisin; Svetlana I. Beketova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with the preparation of environmentally conscious specialists in university an economic profile. Presents the views of scientists A.A. Virbitskiy, I.D. Zverev, I.T. Suravegina, A.N. Zakhlebnyi, S.D. Deryabo, V.A. Yasvin on the essence of the principles and conditions for the continuous ecological education in the vocational education institutions. Disclosed are psychological and pedagogical aspects of the continuity of ecological and geographical education on an example of studying economic geography in in the university an economic profile, emphasizes a system-function continuity in the development of continuous ecological education. Touches upon problem of insufficient consideration of issues of ecological and geographical nature of the courses in the study of economic and geographic content of students of economic specialties. Attention is paid to the need to use the principle of continuity in the study of the structure of industry, agriculture, transport in the course "Geography and regionalistic", based on interdisciplinary communication, learned before, especially in the study of inter-industry complexes; to mandatory review of national and regional components. Analyzed the course "Ecology" is included in the direction of 38.03.01 "Economy" of GEF. The requirements for the cycle in the natural sciences in the direction of GEF 38.03.01. "Accounting, analysis and audit." Showing the value of the role of optional classes and elective courses on environmental protection and rational nature, taking into account the specifics of vocational schools. Were developed and tested the elective courses program "Problems of continuity in the study of the economic geography of Tatarstan", aimed at formation of the skills of analysis and scientific justification of accommodation of productive forces, study questions of organizing the economy based on ecological and geographical characteristics of the region. Attention is given to solving environmental problems at the regional level, associated with the formation of TPC. Proposed teaching manual "Fundamentals of environmental knowledge in the training of specialists of economic profile", created on the basis of elective courses "Ecology in commercial activities" for students studying "Economics", "Management", "Accounting and audit". The manual focuses on environmental and economic issues in accordance with the economic profile of education: Environmental Management and Marketing; environmental legislation; hygienic rationing; contractual forms and others. Revealed the importance of elective courses in the possibility to contribute in-depth ecological and geographical knowledge of specialists of economic profile to make better decisions in economic activity.